The cosmic environment overtakes the local density in shaping galaxy star formation. Issue 2 (14th December 2021) - Ren, Jian; Pan, Zhizheng; Zheng, X Z; Qin, Jianbo; Shi, D D; Gonzalez, Valentino; Bian, Fuyan; Huang, Jia-Sheng; Fang, Min; Liu, Wenhao; Wen, Run; Zhang, Yuheng; et al.
ABSTRACT: The gas supply from the cosmic web is the key to sustain star formation in galaxies. It remains to be explored how the cosmic large-scale structure (LSS) effects on galaxy evolution at given local environments. We examine galaxy-specific star formation rate as a function of local density in a LSS at z  = 0.735 in the Extended Chandra Deep Field South. The LSS is mapped by 732 galaxies with R < 24 mag and redshift at 0.72 ≤ z ≤ 0.75 collected from the literature and our spectroscopic observations with Magellan/IMACS, consisting of five galaxy clusters/groups and surrounding filaments over an area of 23.9 × 22.7 co-moving Mpc 2 . The spread of spectroscopic redshifts corresponds a velocity dispersion of 494 km s −1, indicating the LSS likely to be a thin sheet with a galaxy density ≳ 3.9 times that of the general field. These clusters/groups in this LSS mostly exhibit elongated morphologies and multiple components connected with surrounding filaments. Strikingly, we find that star-forming galaxies in the LSS keep star formation at the same level as field, and show no dependence on local density but stellar mass. Meanwhile, an increasing fraction of quiescent galaxies is detected at increasing local density in both the LSS and the field, consistent with the expectation that galaxy mass and local dense environment hold the key to quench star formation. Combined together, we conclude that the cosmic environment of the LSS overtakes the local environment in remaining galaxy star formation to the level of the field.